Entkolonialisierung und Agrarreform in Marokko.: Das Beispiel des Gharb - Popp, Herbert (ERDKUNDE, 1980)
During the French colonial rule the agrarian landscape of Morocco had been changed to a considerable degree by the activities of European settlers (’colons’): more than one million hectares of arable land belonged to foreigners. After Morocco became independent in 1956 a policy of expropriation of foreign landed property began very slowly and went on till 1973. Parallel to the measures of decolonisation the activities of a land reform began. From 1956-1966 they were carried out in a very slow and unsystematic way, since 1966 they have been realized on a larger scale. The area of the Gharb plain (northwestern Morocco), which is studied in more detail, was already a zone of agrarian transition in the colonial period and has remained one since then, especially in the post-colonial phase. Changes in the pattern of landed properties after independance and the effects of those changes on the social situation are described, as well as the changes in agricultural production. Above all the results of the strong intervention in agriculture by the Morrocan state within the framework of land reform and reform of the farming system in the modern irrigation sector are discussed in greater detail.